Evolving telemedicine practice: experiences of health care workers during covid-19 pandemic (2021)
Background: Telemedicine is employed in patient care when direct physical contact is not possible or discouraged, as was seen during the COVID-19 pandemic. The use of smartphone technology could make telemedicine affordable and available in low and medium-income countries (LMICs). However, the evolution of telemedicine care depends on multiple factors. Aim: To explore the practice of telemedicine by Nigerian health care workers (HCWs) during the COVID-19 pandemic Methods: A cross-sectional study of the Nigerian HCWs on telemedicine practice in patient care during the COVID-19 pandemic period. Recruitment of respondents was done through dedicated WhatsApp and Telegram social media platforms for HCWs over a period of 40 days (May 1st and June 10th, 2020).Results: A total of 481 HCWs participated in the study consisting of 153(31.8%) doctors, 150(31.2%) nurses and 178(37%) other HCWs. Though 89.2% of the HCWs agreed that telemedicine is important, it was only 266 (55.3%) that practiced telemedicine, phone consultation was the form of telemedicine used in all the health institutions. Telemedicine was practiced more by doctors 91(18.9%), nurses 79(16.4%) and pharmacists 35(7.3%) than other groups of health care workers. Inadequate COVID-19 screening test and lack of personal protective equipment were strong motivators for the attending HCWs to practice telemedicine. Conclusion: There was widespread use of phone consultation by all cadres of health care workers during the pandemic. Hence there should be a health policy that will encourage greater use and acceptance of telemedicine in clinical practice and in the patients care beyond the pandemic period